Characterization and Function Analysis of the Beta-Carotene Oxygenase-like Genes in Carotenoids Metabolism of the Ridgetail White Prawn Exopalaemon carinicauda - Jin, Yue; Yu, Yang; Zhang, Chengsong; Li, Shihao; Zhang, Xiaojun; Li, Fuhua (Frontiers in Physiology, 2020)
Carotenoids are almost universally distributed in living organisms. The oxidative metabolism by carotene oxygenase contributes to the metabolic processes of carotenoids. 15,15′-beta-carotene oxygenase (BCO1) and 9′,10′-beta-carotene oxygenase (BCO2) are two important carotenoid oxygenases. In order to understand the function of carotenoid oxygenases in crustaceans, seven genes encoding carotenoid oxygenases (named EcBCO-like) were isolated from the transcriptome database of Exopalaemon carinicauda. After phylogenetic analysis with carotenoid oxygenases reported in other species, EcBCO-like1, EcBCO-like3 and EcBCO-like6 were chosen for further functional study. The prawns after EcBCO-like1 knockdown suffered continuous death, which suggested its important role for the survival of the animals. For the prawns after EcBCO-like3 knockdown, no phenotype change was observed. The prawns after EcBCO-like6 knockdown showed color changes in their hepatopancreas when they were fed with carotenoids-containing diet, and the content of carotenoid in their hepatopancreas was much higher than that in the control prawns. The present study will pave the way for further understanding the carotenoids metabolism in the prawns.